Multilayer electronic component
By using a second electrode layer containing SiC in the outer electrode of the multilayer ceramic capacitor and using glass of different compositions in the first and second electrode layers, the reliability problems caused by glass erosion of Cu sintered electrodes and the reduction of glass transition temperature are solved, and the effect of improving moisture and chemical resistance is achieved.
Patent Information
- Application Number
- CN202411220110.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-07
- Filing Date
- 2024-09-02
- Publication Date
- 2025-03-07
AI Technical Summary
The Cu sintered electrode glass of the multi-layer ceramic capacitor is eroded by the plating solution, resulting in deterioration of reliability, and when the glass transition temperature decreases, the glass cannot penetrate fully into the main body, resulting in deterioration of moisture resistance reliability.
A second electrode layer including Cu and SiC is employed, and the area fraction of SiC is greater than or equal to 5% and less than or equal to 20% to improve chemical resistance and moisture resistance reliability, and ensure more favorable characteristics of the outer electrode by using glass of different compositions in the first and second electrode layers.
It effectively prevents the deterioration of reliability caused by the penetration of plating solutions and moisture, improves the moisture and chemical resistance of multi-layer electronic components, and ensures the stability and performance of components.
Smart Images

Figure CN119581223A_ABST
Abstract
Description
[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0118899 filed on September 7, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] The present disclosure relates to a multi-layer electronic assembly. Background Art
[0003] Multilayer ceramic capacitors (MLCC, a type of multilayer electronic component) are chip capacitors mounted on printed circuit boards for various electronic products for charging or discharging, including display devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smart phones, mobile phones, circuits such as on-board chargers (OBC) DC-DC converters for electric vehicles, and the like.
[0004] The glass included in the base electrode layer of the existing external electrode is mainly formed of a network forming material such as Si and Al, and an alkali metal or an alkaline earth metal may be added to lower the glass transition temperature Tg. However, in the case of forming a plating layer on the base electrode layer, reliability degradation may occur due to glass corrosion, and if the glass transition temperature is excessively lowered, the glass may not be sufficiently infiltrated into the body, resulting in moisture resistance reliability degradation.
[0005] Therefore, there is a need to improve the structure of the external electrode to prevent reliability degradation due to penetration of a plating solution or external moisture. Summary of the invention
[0006] An aspect of the present disclosure is to solve the problem of reliability degradation of a multilayer electronic component due to corrosion of glass of a Cu sintered electrode by a plating solution.
[0007] Another aspect of the present disclosure is to solve the problem that when the glass transition temperature of the glass of the Cu sintered electrode is lowered, the moisture resistance reliability of the multilayer electronic component is deteriorated because the glass cannot sufficiently penetrate into the body.
[0008] However, the purpose of the present disclosure is not limited to the foregoing and may be more easily understood in the course of describing specific exemplary embodiments in the present disclosure.
[0009] According to one aspect of the present disclosure, a multilayer electronic component includes: a main body, including a dielectric layer and internal electrodes alternately arranged with the dielectric layer; and an external electrode arranged on the main body, wherein the external electrode includes a first electrode layer in contact with the internal electrode and a second electrode layer arranged on the first electrode layer, the first electrode layer includes Cu, the second electrode layer includes Cu and SiC, and the area fraction of SiC in the second electrode layer is greater than or equal to 5% and less than or equal to 20%.
[0010] According to another aspect of the present disclosure, a multilayer electronic component includes: a main body, including a dielectric layer and internal electrodes alternately arranged with the dielectric layer; and an external electrode arranged on the main body, wherein the external electrode includes a first electrode layer in contact with the internal electrode and a second electrode layer arranged on the first electrode layer, the first electrode layer includes Cu and a first glass, the second electrode layer includes Cu, SiC, and a second glass, and the composition of the first glass is different from the composition of the second glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The above and other aspects, features and advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:
[0012] Figure 1 is a perspective view schematically illustrating a multilayer electronic component according to an exemplary embodiment;
[0013] Figure 2 is along Figure 1 A cross-sectional view taken along line II' in FIG.
[0014] Figure 3 is along Figure 1 A cross-sectional view taken along line II-II';
[0015] Figure 4 is an exploded perspective view of a main body according to an exemplary embodiment;
[0016] Figure 5 yes Figure 2 A magnified view of the P region in FIG.
[0017] Figure 6 yes Figure 2 A magnified view of the variation of the P region in FIG.
[0018] Figure 7 is an image of a cross section of the second electrode layer taken with a scanning electron microscope (SEM) when the SiC area fraction exceeds 20%; and
[0019] Figure 8This is an image of the cross section of the second electrode layer taken with a SEM when the SiC area fraction satisfies 5% or more and 20% or less. DETAILED DESCRIPTION
[0020] Hereinafter, exemplary embodiments of the inventive concept will be described in detail with reference to the accompanying drawings. However, the inventive concept may be illustrated in many different forms and should not be construed as being limited to the specific exemplary embodiments set forth herein. On the contrary, these exemplary embodiments are provided so that this disclosure will be thorough and complete, and the scope of the inventive concept will be fully conveyed to those skilled in the art. In the accompanying drawings, for the sake of clarity, the shapes and sizes of the elements may be exaggerated, and the same reference numerals will always be used to represent the same or similar elements.
[0021] In order to clarify the present disclosure, throughout the specification, parts irrelevant to the description are omitted, and the same reference numerals refer to the same elements, and in the drawings, the thickness of layers, films, panels, regions, etc. are exaggerated for clarity. In addition, in the drawings, the same reference numerals refer to the same elements although they are shown in different drawings. Throughout the specification, unless explicitly described to the contrary, the word "include" and variations such as "contain" or "comprise" will be understood to imply the inclusion of the elements but not the exclusion of any other elements.
[0022] In the drawings, the first direction is a direction or a thickness direction in which the first internal electrodes and the second internal electrodes are alternately arranged with the dielectric layer interposed therebetween, and the second direction and the third direction are perpendicular to the first direction, wherein the second direction can be defined as a length direction and the third direction can be defined as a width direction.
[0023] A multilayer electronic component 100 according to an exemplary embodiment of the present disclosure may include: a main body, including a dielectric layer 111 and internal electrodes 121 and 122 alternately arranged with the dielectric layer; and external electrodes 130 and 140, arranged on the main body, wherein the external electrode includes a first electrode layer 131 in contact with the internal electrode and a second electrode layer 132 arranged on the first electrode layer, the first electrode layer includes Cu (denoted as 131a), and the second electrode layer includes Cu (denoted as 132a) and SiC (denoted as 132c).
[0024] The body 110 includes a dielectric layer 111 and internal electrodes 121 and 122 alternately disposed with the dielectric layer 111 .
[0025] Although the specific shape of the body 110 is not particularly limited, as shown in the figure, the body 110 may have a hexahedral shape or the like. Due to the shrinkage of the ceramic powder particles included in the body 110 during the sintering process, the body 110 may not have a perfectly straight hexahedral shape, but may have a substantially hexahedral shape.
[0026] The main body 110 may include a first surface 1 and a second surface 2 that face each other in a first direction, a third surface 3 and a fourth surface 4 that are connected to the first surface 1 and the second surface 2 and face each other in a second direction, and a fifth surface 5 and a sixth surface 6 that are connected to the first surface 1 and the second surface 2 and the third surface 3 and the fourth surface 4 and face each other in a third direction.
[0027] The plurality of dielectric layers 111 forming the main body 110 are in a sintered state, and adjacent dielectric layers 111 may be integral, such that their boundaries may not be easily distinguishable without using a scanning electron microscope (SEM).
[0028] According to an exemplary embodiment of the present disclosure, the material for forming the dielectric layer 111 is not limited as long as sufficient electrostatic capacitance can be obtained. For example, a barium titanate-based material, a lead composite perovskite-based material, or a strontium titanate-based material can be used. The barium titanate-based material may include BaTiO3-based ceramic powder, and the ceramic powder may include BaTiO3 and (Ba 1-x Ca x )TiO3 (0 < x < 1), Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1) or Ba(Ti 1-y Zr y )O3 (0 < y < 1).
[0029] In addition, as the material for forming the dielectric layer 111, various ceramic additives, organic solvents, binders, dispersants, etc. may be added to a powder such as barium titanate (BaTiO3) according to the purpose of the present disclosure.
[0030] The average thickness td of the dielectric layer 111 is not particularly limited.
[0031] For the purpose of miniaturization and high capacitance of the multilayer electronic component 100, the average thickness td of the dielectric layer 111 may be less than or equal to 0.35 μm, and for the purpose of improving the reliability of the multilayer electronic component 100 at high temperature and high voltage, the average thickness of the dielectric layer 111 may be greater than or equal to 2 μm.
[0032] The average thickness td of the dielectric layer 111 may refer to the average thickness td of the dielectric layer 111 disposed between the first internal electrode 121 and the second internal electrode 122.
[0033] The average thickness td of the dielectric layer 111 can be measured by scanning an image of a cross section of the body 110 in the length direction-thickness direction with a scanning electron microscope (SEM) at a magnification of 10000 times. More specifically, the average value can be measured by measuring the thickness of one dielectric layer at 30 equally spaced points in the length direction in the scanned image. The 30 equally spaced points can be specified in the capacitor forming portion Ac. In addition, if the average value is measured by extending the measurement of the average value to 10 dielectric layers, the average thickness of the dielectric layer can be more generalized.
[0034] The body 110 may include a capacitor forming portion Ac and cover portions 112 and 113 formed above and below the capacitor forming portion Ac in a first direction, wherein the capacitor forming portion Ac is formed inside the body 110 and forms a capacitor using first and second internal electrodes 121 and 122 alternately arranged with a dielectric layer 111 interposed therebetween.
[0035] In addition, the capacitance forming part Ac is a portion that contributes to forming the capacitance of the capacitor, and may be formed by repeatedly stacking a plurality of first and second internal electrodes 121 and 122 with the dielectric layer 111 interposed therebetween.
[0036] In an exemplary embodiment, the upper cover portion 112 may be disposed on one surface of the capacitance forming portion Ac in the first direction, and the lower cover portion 113 may be disposed on the other surface of the capacitance forming portion Ac in the first direction.
[0037] The upper cover portion 112 and the lower cover portion 113 may be formed by stacking a single dielectric layer or two or more dielectric layers on the upper and lower surfaces of the capacitance forming portion Ac in the thickness direction, respectively, and may serve to prevent damage to the internal electrodes due to physical stress or chemical stress.
[0038] The upper cover part 112 and the lower cover part 113 do not include an internal electrode, and may include the same material as that of the dielectric layer 111 .
[0039] That is, the upper cover part 112 and the lower cover part 113 may include a ceramic material, for example, a barium titanate (BaTiO 3 )-based ceramic material.
[0040] In addition, the average thickness tc of the cover parts 112 and 113 may not be particularly limited. However, the average thickness tc of the cover parts 112 and 113 may be equal to or less than 15 μm in order to more easily achieve miniaturization and high capacitance of the multilayer electronic component.
[0041] The average thickness tc of the cover portions 112 and 113 may refer to a dimension in the first direction, and may be a value obtained by averaging dimensions of the cover portion 112 or 113 measured at five equally spaced points above or below the capacitance forming portion Ac.
[0042] In an exemplary embodiment, the edge portions 114 and 115 may be disposed on one surface and the other surface of the capacitance forming portion Ac in the third direction.
[0043] Reference Figure 3 , the edge portions 114 and 115 may include an edge portion 114 disposed on one surface of the capacitance forming portion Ac and an edge portion 115 disposed on another surface of the capacitance forming portion Ac. That is, the edge portions 114 and 115 may be disposed on both surfaces of the capacitance forming portion Ac in the third direction (width direction).
[0044] like Figure 3 As shown in , the edge portions 114 and 115 may refer to regions between both ends of the first and second internal electrodes 121 and 122 and a boundary surface of the body 110 .
[0045] The edge portions 114 and 115 may generally serve to prevent the inner electrodes from being damaged due to physical stress or chemical stress.
[0046] The edge portions 114 and 115 may be formed when forming the internal electrodes by coating a conductive paste on regions other than regions where the edge portions are to be formed on the ceramic green sheets.
[0047] In addition, in order to suppress the step difference caused by the internal electrodes 121 and 122, edge portions 114 and 115 can be formed by cutting the internal electrodes after stacking to expose one surface and the other surface of the capacitor forming portion Ac in the third direction and then stacking a single dielectric layer or two or more dielectric layers on the two surfaces of the capacitor forming portion Ac in the third direction (width direction).
[0048] In addition, the width of the edge portions 114 and 115 may not be particularly limited. However, the average width of the edge portions 114 and 115 may be equal to or less than 15 μm in order to more easily achieve miniaturization and high capacitance of the multilayer electronic component.
[0049] The average width of the edge portions 114 and 115 may refer to an average size of the edge portions 114 and 115 in the third direction, and may be a value obtained by averaging sizes of the edge portions 114 and 115 measured at five equally spaced points on the surface of the capacitance forming portion Ac.
[0050] The internal electrodes 121 and 122 are alternately arranged with the dielectric layers 111 in the first direction.
[0051] The internal electrodes 121 and 122 may include a first internal electrode 121 and a second internal electrode 122. The first internal electrode 121 and the second internal electrode 122 may be alternately disposed to face each other with the dielectric layer 111 interposed therebetween, and may be connected to the third surface 3 and the fourth surface 4 of the body 110, respectively. Specifically, one end of the first internal electrode 121 may be connected / extended to the third surface, and one end of the second internal electrode 122 may be connected / extended to the fourth surface. That is, in an exemplary embodiment, the internal electrodes 121 and 122 may contact the third surface 3 or the fourth surface 4.
[0052] like Figure 1 and Figure 2 As shown in , the first internal electrode 121 may be spaced apart from the fourth surface 4 and may be exposed to the third surface 3, and the second internal electrode 122 may be spaced apart from the third surface 3 and may be exposed to the fourth surface 4. The first external electrode 130 may be disposed on the third surface 3 of the body and connected to the first internal electrode 121, and the second external electrode 140 may be disposed on the fourth surface 4 of the body and connected to the second internal electrode 122.
[0053] That is, the first internal electrode 121 is not connected to the second external electrode 140 but to the first external electrode 130, and the second internal electrode 122 is not connected to the first external electrode 130 but to the second external electrode 140. Therefore, the first internal electrode 121 may be formed to be spaced apart from the fourth surface 4 by a predetermined distance, and the second internal electrode 122 may be formed to be spaced apart from the third surface 3 by a predetermined distance. In this case, the first internal electrode 121 and the second internal electrode 122 may be electrically isolated from each other by the dielectric layer 111 disposed therebetween.
[0054] Reference Figure 4 , the body 110 may be formed by alternately stacking ceramic green sheets having the first internal electrodes 121 formed thereon and ceramic green sheets having the second internal electrodes 122 formed thereon and then sintering the green sheets.
[0055] The material for forming the internal electrodes 121 and 122 is not particularly limited, and a material having excellent conductivity may be used. For example, the internal electrodes 121 and 122 may include at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.
[0056] In addition, the internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes including at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof on a ceramic green sheet. The printing method of the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present disclosure is not limited thereto.
[0057] The average thickness te of the internal electrodes 121 and 122 is not particularly limited and may vary according to the purpose. In order to miniaturize the multilayer electronic component 100, the average thickness te of the internal electrodes 121 and 122 may be less than or equal to 0.35 μm, and in order to improve the reliability of the multilayer electronic component 100 under high temperature and high voltage, the average thickness te of the internal electrodes 121 and 122 may be greater than or equal to 2 μm.
[0058] The average thickness te of the internal electrodes 121 and 122 is obtained as follows. In an image of a cross section of the main body 110 in the length direction and the thickness direction taken at the center of the main body 110 in the width direction scanned by a scanning electron microscope, among the internal electrode layers, based on one internal electrode layer at a reference point where the center line of the main body in the length direction and the center line of the main body in the thickness direction intersect, a total of five internal electrode layers including the one internal electrode and its two upper layers and two lower layers are extracted, and then based on the reference point where the center line of the main body in the length direction and the center line of the main body in the thickness direction intersect, five points including the reference point and its two left points and two right points are determined at equal intervals, and thereafter, the thickness at each point is measured and averaged.
[0059] The external electrodes 130 and 140 are disposed on the body 110 .
[0060] The external electrodes 130 and 140 may include a first external electrode 130 in contact with the third surface 3 of the body 110 and a second external electrode 140 in contact with the fourth surface 4 of the body 110 .
[0061] Hereinafter, various exemplary embodiments of the structure of the external electrode are described based on the first external electrode 130. The description of the first external electrode 130 may also be applied to the second external electrode 140.
[0062] The first external electrode 130 may include a first electrode layer 131 contacting the first internal electrode 121 and a second electrode layer 132 disposed on the first electrode layer 131 .
[0063] The first electrode layer 131 includes Cu and may be used to ensure electrical connectivity with the first internal electrode 121. Here, the Cu included in the first electrode layer 131 may form an alloy, an intermetallic compound, or a solid solution with a conductive metal included in the first internal electrode 121. For example, when the internal electrodes 121 and 122 include Ni, a Ni-Cu intermetallic compound may be formed at an interface between the first internal electrode 121 and the first electrode layer 131, and thus, electrical connectivity between the external electrode and the internal electrode may be improved. In addition, the first electrode layer may be formed by applying a conductive paste including Cu and glass to the third surface 3 and the fourth surface 4 of the body 110 and sintering, but is not limited thereto.
[0064] The second electrode layer 132 may be disposed on the first electrode layer 131. The second electrode layer may include Cu and SiC. SiC may improve the chemical resistance of the second electrode layer 132 and delay the sintering of Cu to control sintering shrinkage, and thus, SiC may be used to improve density. Therefore, when the plating layers 133 and 134 are disposed on the second electrode layer 132, the chemical resistance to the plating solution may be improved, and when the conductive resin layer 135 is disposed on the second electrode layer 132, the surface roughness of the second electrode layer 132 may be improved, thereby improving the adhesion between the second electrode layer 132 and the conductive resin layer 135.
[0065] The SiC included in the second electrode layer 132 is a material resistant to thermal shock and has excellent chemical stability. When SiC is included in the second electrode layer 132, damage to the first internal electrode 121 due to thermal shock and plating solution penetration can be prevented, thereby improving the strength, chemical resistance, and moisture resistance reliability of the multilayer electronic component 100.
[0066] In particular, as in the exemplary embodiment, when the second electrode layer 132 includes Si and Al and further includes an alkali metal or an alkaline earth metal, a decrease in chemical resistance and moisture resistance reliability may be prevented.
[0067] That is, when the second electrode layer 132 includes Si and Al, further includes an alkali metal or an alkaline earth metal, and further includes SiC, the effect of improving the chemical resistance and moisture resistance reliability of the multilayer electronic component 100 may become more significant.
[0068] In addition, since SiC is a material resistant to thermal shock as described above, SiC may not be deformed even after sintering the first external electrode 130. That is, the shape of the introduced SiC and the shape of the SiC present in the second electrode layer 132 of the multilayer electronic component 100 may be substantially the same. In addition, SiC may be added in the form of a powder having spherical particles to control uniform sintering shrinkage of the second electrode layer 132, and at least some particles of SiC of the second electrode layer 132 according to an exemplary embodiment may be spherical.
[0069] In addition, if the proportion of SiC in the second electrode layer 132 is excessive, the sintering of Cu in the second electrode layer may become insufficient due to excessive sintering delay, which may actually deteriorate the moisture resistance reliability of the multilayer electronic component 100. Therefore, in an exemplary embodiment, the sintering property of the second electrode layer 132 may be appropriately controlled by adjusting the area fraction of SiC in the second electrode layer 132 to be less than or equal to 20%, and thus, the deterioration of the moisture resistance reliability of the multilayer electronic component 100 may be prevented. In addition, the area fraction of SiC in the second electrode layer 132 may be greater than or equal to 5% to improve the adhesion strength to the conductive resin layer 135 or improve the moisture resistance reliability by providing sufficient roughness to the surface of the second electrode layer 132.
[0070] In addition, SiC may be substantially included only in the second electrode layer 132, and may not be included in the first electrode layer 131. That is, in an exemplary embodiment, the first electrode layer 131 may include SiC at an area fraction of less than 1%. The area fraction of SiC included in the first electrode layer 131 may be measured by a method similar to the method of measuring the area fraction of SiC in the second electrode layer 132 disclosed herein. Even if not described in the present disclosure, other methods and / or tools understood by a person of ordinary skill in the art may be used.
[0071] In addition, the first electrode layer 131 may include a first glass (denoted as 131b), and the second electrode layer 132 may include a second glass (denoted as 132b). In an exemplary embodiment, the first glass included in the first electrode layer 131 and the second glass included in the second electrode layer 132 may have different compositions. Therefore, the first electrode layer 131 and the second electrode layer 132 may include glasses having different characteristics, thereby ensuring more favorable characteristics of the external electrode 130.
[0072] Specifically, the first glass may include Ba and Zn, and the second glass may include Si and Al. Since the first electrode layer 131 includes the first glass including Ba and Zn, the first glass has excellent adhesion to the dielectric layer 111 included in the body 110, thereby preventing external moisture from penetrating into the multilayer electronic component 100, and since the second electrode layer 132 includes the second glass including Si and Al, the second glass may suppress sintering shrinkage, thereby improving the densification of the external electrode 130, thereby improving the chemical resistance of the multilayer electronic component 100 to the plating solution.
[0073] The first glass may further include Si and Na in addition to Ba and Zn, and the second glass may further include Sr and Ba in addition to Si and Al. The elements contained in the first glass and the second glass may exist in the form of oxides and may exist as amorphous glass.
[0074] In addition, since the first glass is a glass containing Ba and Zn, the glass transition temperature Tg of the first glass may be lower than the glass transition temperature Tg of the second glass, which will be described below. Therefore, a portion of the first glass may diffuse into the dielectric layer 111 of the body 110 during the pre-sintering process. That is, in an exemplary embodiment, at least a portion of the end E of the dielectric layer 111 contacting the first electrode layer 131 may include the first glass. Therefore, the adhesion between the first external electrode 130 and the body 110 may be improved.
[0075] In addition, the second electrode layer 132 including the second glass may further include one or more of an alkali metal, an alkaline earth metal, and an oxide thereof to reduce the glass transition temperature Tg. In this case, the glass transition temperature Tg may be reduced by weakening a portion of the Si-Al network structure, but there is a risk that the chemical resistance to the plating solution may deteriorate. Therefore, in an exemplary embodiment of the present disclosure, since the second electrode layer 132 includes SiC, the glass transition temperature Tg may be reduced, and at the same time, the deterioration of the chemical resistance to the plating solution may be prevented.
[0076] In an exemplary embodiment, the average thickness of the second electrode layer 132 may be greater than the average thickness of the first electrode layer 131. By forming the second electrode layer 132 having excellent moisture resistance and chemical resistance to be thicker than the first electrode layer 131, moisture resistance reliability and chemical resistance of the multilayer electronic component 100 are improved without deteriorating adhesion between the first external electrode 130 and the body 110.
[0077] Both the first electrode layer 131 and the second electrode layer 132 include Cu as a conductive metal, but they can be distinguished from an image observed through a scanning electron microscope (SEM).
[0078] Specifically, when an image of a polished cross section of the multilayer electronic component 100 is observed by SEM after polishing the surface of the multilayer electronic component 100 in the length direction-width direction to 1 / 2 of the multilayer electronic component 100 in the thickness direction, for the first external electrode 130, the contrast may be darkened in the order of Cu, the first glass, the second glass, and SiC, based on which the first electrode layer 131 and the second electrode layer 132 may be distinguished from each other. That is, the region including the first glass having the second brightest contrast may be identified as the first electrode layer 131, and the region including the second glass having the third brightest contrast and the SiC having the darkest contrast may be identified as the second electrode layer 132. When the first glass includes Ba and Zn and the second glass includes Si and Al, the difference in contrast may become clearer. The average thickness of the first electrode layer 131 may be obtained by measuring the thickness at various positions in the first electrode layer 131 using a scanning electron microscope (SEM) and averaging the measured thicknesses. Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art may be used. The average thickness of the second electrode layer 132 can be obtained similarly.
[0079] As an example of a method of measuring the area fraction of SiC in the second electrode layer 132, in an image of a polished cross section where the surface of the multilayer electronic component 100 in the length direction-width direction (second direction-third direction) is polished to 1 / 2 of the multilayer electronic component 100 in the thickness direction (first direction), the area of the second electrode layer 132 is specified by the above-mentioned method of distinguishing the first electrode layer 131 from the second electrode layer 132, and then, by analyzing and mapping Si and C elements by scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDS), the area of SiC particles can be measured and the ratio of the area of SiC particles to the area of the second electrode layer 132 can be obtained. This measurement can be performed under the conditions of an acceleration voltage of 15 kV and WD=15 mm, and can be further generalized by dividing the area of the second electrode layer 132 formed on the first electrode layer 131 into three equal parts in the width direction (third direction), measuring the area fraction of SiC in each area, and then obtaining the average value. Even if not described in the present disclosure, other methods and / or tools understood by a person of ordinary skill in the art may be used.
[0080] The shape of SiC in the second electrode layer 132 can also be measured similarly to the method of measuring the area fraction of SiC. Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art can also be used. The ratio of the major axis to the minor axis of the SiC particle can be measured, and when the ratio of the major axis to the minor axis is greater than or equal to 0.9 and less than or equal to 1.1, the SiC particle can be determined to be spherical.
[0081] As an example of a method of measuring the average thickness of the first electrode layer 131 and the average thickness of the second electrode layer 132, in an image of a polished cross section where the surface of the multilayer electronic component 100 in the length direction-width direction (second direction-third direction) is polished to 1 / 2 of the multilayer electronic component 100 in the thickness direction (first direction), the region of the second electrode layer 132 is specified by the above-mentioned method of distinguishing the first electrode layer 131 and the second electrode layer 132, and then, the average value of the size of the first electrode layer 131 in the second direction and the average value of the size of the second electrode layer 132 in the second direction are measured. The measurement of the average thickness of the first electrode layer 131 and the second electrode layer 132 in the second direction can be further generalized by dividing the region of the first electrode layer 131 and the second electrode layer 132 formed on the third surface 3 or the fourth surface 4 of the body 110 into five or more regions in the width direction (third direction) and then obtaining the average value of the size in the second direction.
[0082] In an exemplary embodiment, the first external electrode 130 may further include plating layers 133 and 134 disposed on the second electrode layer 132 .
[0083] The plating layers 133 and 134 are used to improve mounting characteristics. The types of the plating layers 133 and 134 are not particularly limited, and the plating layers 133 and 134 may include one or more of Ni, Sn, Pd, and alloys thereof and may be formed of a plurality of layers.
[0084] For a specific example of the plating layers 133 and 134, the plating layers may be Ni plating layers or Sn plating layers, and may be formed by sequentially forming Ni plating layers and Sn plating layers on the second electrode layer 132, or may be formed by sequentially forming Sn plating layers, Ni plating layers, and Sn plating layers. In addition, the plating layers may also include a plurality of Ni plating layers and / or a plurality of Sn plating layers.
[0085] Reference Figure 5 In an exemplary embodiment, the first plating layer 133 including Ni may be disposed on the second electrode layer 132. Thus, when the multilayer electronic component 100 is mounted on a board, thermal shock due to solder reflow may be mitigated.
[0086] Reference Figure 5 In an exemplary embodiment, the second plating layer 134 including Sn may be disposed on the first plating layer 133 including Ni. The second plating layer 134 may include Sn and may serve to improve mounting characteristics when disposed as the outermost layer of the external electrodes 130 and 140.
[0087] In an exemplary embodiment, the first external electrode 130 may further include a conductive resin layer 135 (eg, Figure 6As shown), and the conductive resin layer 135 may include a conductive metal and a resin.
[0088] The conductive resin layer 135 may be directly formed on the second electrode layer 132 , and in this case, the plating layers 133 and 134 may be formed on the conductive resin layer 135 .
[0089] The conductive metal may include one or more of Cu, Ni, Ag, Sn, and Cr, and the conductive metal may exist in a dispersed form within the resin of the conductive resin layer 135 .
[0090] The resin may include a resin having strong heat resistance. For example, the resin may include one or more of phenolic resin, urea resin, diallyl phthalate resin, melamine resin, guanamine resin, unsaturated polyester resin, polyurethane resin, epoxy resin, acrylic resin, ethyl cellulose resin, amino alkyd resin, melamine-urea co-condensation resin, silicone resin and polysiloxane resin, but is not limited thereto.
[0091] The conductive resin layer 135 may serve to protect the multilayer electronic component 100 from stress due to bending that may occur when the multilayer electronic component 100 is mounted on a board and stress due to solder reflow.
[0092] In addition, when the second electrode layer 132 includes Cu, the second glass, and SiC, roughness may be provided to the surface of the second electrode layer 132 , and thus, adhesion between the second electrode layer 132 and the conductive resin layer 135 may be improved.
[0093] In addition, even when the conductive resin layer 135 is formed on the second electrode layer 132, it is necessary to appropriately adjust the area fraction of SiC included in the second electrode layer 132. For example, if the area fraction of SiC of the second electrode layer 132 is less than 5%, the effect of controlling the sintering shrinkage of the second electrode layer 132 may not be significant and the surface roughness of the second electrode layer 132 may not be sufficiently provided, and if the ratio of SiC in the second electrode layer 132 exceeds 20%, there may be a risk that the second electrode layer 132 may not be sintered. Therefore, in an exemplary embodiment, the area fraction of SiC of the second electrode layer 132 may be adjusted to be greater than or equal to 5% and less than or equal to 20% to provide appropriate roughness to the surface of the second electrode layer 132, thereby improving adhesion to the conductive resin layer 135 and ensuring appropriate sinterability at the same time.
[0094] Hereinafter, an experimental example of evaluating the densification and roughness of the second electrode layer 132 , the adhesion strength and solubility of the second electrode layer 132 and the conductive resin layer 135 by changing the area fraction of SiC in the second electrode layer 132 is described.
[0095] The powder for forming the dielectric layer is mixed with a dispersant using ethanol and toluene as solvents, and then mixed with a binder to manufacture a ceramic green sheet. The Ni electrode is printed and laminated on the formed ceramic green sheet to form a sheet, and the sheet is stacked, pressed and cut to form a body. The sheet is calcined in an air atmosphere at 400°C, and then sintered for about 1 hour at about 1300°C or lower and a hydrogen (H2) concentration of 2.0% or lower. A conductive paste including copper powder and a glass material for forming a first glass is applied and burned out at a temperature of 600°C to 800°C for 1 to 2 hours, and a conductive paste including copper powder, a glass material for forming a second glass and SiC spherical powder particles is applied and burned out for a second time at a temperature of 600°C to 800°C for 1 to 2 hours.
[0096] In the conductive paste for forming the first electrode layer 131, the glass frit for forming the first glass has a content of about 3 wt % to 15 wt % and has components including Ba, Zn, Si, Na, etc., and in the conductive paste for forming the second electrode layer 132, the glass frit for forming the second glass has a content of about 3 wt % to 15 wt % and has components including Si, Al, Sr, Ba, etc. The conductive paste for forming the first electrode layer 131 and the conductive paste for forming the second electrode layer 132 are mixed with a binder and an additive in addition to the aforementioned components.
[0097] In addition, in the experimental example to be described below, in an image of a polished cross section in which the surface of the multilayer electronic component 100 in the length direction-width direction (second direction-third direction) is polished to 1 / 2 of the multilayer electronic component 100 in the thickness direction (first direction), the area of the second electrode layer 132 is specified by the above-mentioned method of distinguishing the first electrode layer 131 and the second electrode layer 132, and then, the Si and C elements are mapped by scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDS) analysis, and the area fraction of SiC is measured by measuring the area of SiC particles and calculating the ratio of the area of the SiC particles to the area of the second electrode layer 132. This measurement is performed under the conditions of an acceleration voltage of 15 kV and WD=15 mm, and the area of the second electrode layer 132 formed on the first electrode layer 131 is divided into three equal parts in the width direction (third direction), and the area fraction of SiC in each area is measured, and then the average value is taken.
[0098] (Experimental Example 1)
[0099] Figure 7 is an image of a cross section of the second electrode layer 132 taken using a scanning electron microscope (SEM) when the SiC area fraction exceeds 20%.
[0100] Reference Figure 7, it can be seen that the proportion of SiC in the second electrode layer 132 is excessive and the sintering degree of Cu is insufficient, resulting in the deterioration of the wettability of the second glass.
[0101] Figure 8 This is an image of a cross section of the second electrode layer taken using a SEM when the SiC area fraction satisfies 5% or more and 20% or less.
[0102] Reference Figure 8 , the ratio of SiC in the second electrode layer 132 is appropriate and the sintering degree of Cu is appropriate, thereby ensuring appropriate densification of the second electrode layer 132 .
[0103] (Experimental Example 2)
[0104] Table 1 shows the results of measuring the surface roughness of the second electrode layer 132 according to the SiC area fraction.
[0105] For the surface roughness, in the image of the polished cross section where the surface of the multilayer electronic component 100 in the length direction-width direction (second direction-third direction) is polished to 1 / 2 in the thickness direction (first direction) of the multilayer electronic component 100. The roughness of the surface of the second electrode layer 132 (interface with the conductive resin layer or the plating layer) was measured, and the arithmetic mean roughness Ra, the maximum height roughness Rmax, and the 10-point average roughness Rz were calculated according to ISO468 and are listed in Table 1.
[0106] [Table 1]
[0107] SiC area fraction Ra(μm) Rmax(μm) Rz(μm) 0% 1.2 10 8 Less than 5% 1.2 10 8 Greater than or equal to 5% and less than or equal to 20% 2 17 12 Greater than 20% 4 or more 30 or more 20 or more
[0108] Referring to Table 1, it can be seen that when the SiC area fraction is less than 5%, the effect of improving the surface roughness of the second electrode layer 132 is insufficient. In addition, it can be seen that when the SiC area fraction exceeds 20%, the surface roughness increases excessively and becomes irregular. This is considered to be caused by the second electrode layer 132 being rarely sintered due to the excess SiC. As a result, it can be confirmed that when the area fraction of SiC in the second electrode layer 132 is greater than or equal to 5% and less than or equal to 20%, the surface roughness of the second electrode layer 132 can be improved and appropriate sintering properties can be ensured.
[0109] (Experimental Example 3)
[0110] Table 2 shows the results of evaluating the adhesion strength after forming the conductive resin layer 135 on the second electrode layer 132. For the adhesion strength, a paste including copper and epoxy resin was applied to the second electrode layer 132 to form the conductive resin layer 135 and mounted on a substrate, and the maximum strength when the second electrode layer 132 was removed was measured by applying stress to the substrate in a horizontal direction with a tensile strength meter.
[0111] [Table 2]
[0112] SiC area fraction <![CDATA[Strength (N / mm 2 )]]> 0% 15 Less than 5% 15 Greater than or equal to 5% and less than or equal to 20% 30 Greater than 20% 40
[0113] Referring to Table 2, it can be seen that the adhesion strength improves as the area fraction of SiC increases. Combining the results of Table 1 with the results of Table 2, it can be confirmed that when the area fraction of SiC in the second electrode layer 132 increases, the surface roughness of the second electrode layer 132 increases, and as a result, the adhesion strength of the second electrode layer 132 and the conductive resin layer 135 improves. However, in order to sufficiently improve the surface roughness of the second electrode layer 132 and the adhesion strength between the second electrode layer 132 and the conductive resin layer 135, the area fraction of SiC in the second electrode layer 132 is preferably greater than or equal to 5%.
[0114] (Experimental Example 4)
[0115] [Table 3]
[0116] SiC area fraction Solubility (%) 0% 14% Less than 5% 13% Greater than or equal to 5% and less than or equal to 20% 1.00% Greater than 20% 0.1%
[0117] Solubility (%) The mass of the second electrode layer 132 was calculated, and after the second electrode layer 132 was formed, the second electrode layer 132 was immersed in distilled water, and the masses before and after the immersion were measured.
[0118] Referring to Table 3, it can be seen that as the area fraction of SiC in the second electrode layer 132 increases, the solubility decreases, and thus, the moisture resistance reliability improves. In particular, it can be seen that when the area fraction of SiC in the second electrode layer 132 is greater than or equal to 5%, the effect of reducing the solubility is significant. That is, it can be confirmed that when the area fraction of SiC in the second electrode layer 132 is greater than or equal to 5%, the effect of improving the moisture resistance reliability of the multilayer electronic component 100 is significant.
[0119] One of the various effects of the present disclosure is that in a two-layer sintered electrode structure having a first electrode layer and a second electrode layer structure including Cu, the second electrode layer includes SiC, and the area fraction of SiC in the second electrode layer is adjusted, thereby improving the chemical resistance and moisture resistance reliability of the multilayer electronic component.
[0120] One of the various effects of the present disclosure is that in a two-layer sintered electrode structure having a first electrode layer and a second electrode layer structure including Cu, the second electrode layer includes SiC and changes the composition of the glass included in the first electrode layer and the second electrode layer, thereby improving the chemical resistance and moisture resistance reliability of the multilayer electronic component.
[0121] While exemplary embodiments have been shown and described above, it will be readily apparent to those skilled in the art that modifications and variations may be made without departing from the scope of the present disclosure as defined by the appended claims.
Claims
1. A multilayer electronic component comprising: A main body, comprising a dielectric layer and inner electrodes arranged alternately with the dielectric layer; as well as an outer electrode, disposed on the body, The outer electrode comprises a first electrode layer in contact with the inner electrode and a second electrode layer disposed on the first electrode layer. The first electrode layer includes Cu, the second electrode layer includes Cu and SiC, and The area fraction of SiC in the second electrode layer is greater than or equal to 5% and less than or equal to 20%.
2. The multilayer electronic component according to claim 1, wherein The first electrode layer includes SiC with an area fraction of less than 1%.
3. The multilayer electronic component according to claim 1, wherein: The first electrode layer further includes a first glass, the second electrode layer further includes a second glass, and the first glass has a composition different from a composition of the second glass.
4. The multilayer electronic component according to claim 1, wherein: The first electrode layer further includes a first glass including Ba and Zn, and the second electrode layer further includes a second glass including Si and Al.
5. The multilayer electronic component according to claim 4, wherein: At least a portion of an end portion of the dielectric layer in contact with the first electrode layer includes the first glass.
6. The multilayer electronic component according to claim 1, wherein At least some of the SiC is spherical.
7. The multilayer electronic component according to claim 1, wherein: An average thickness of the second electrode layer is greater than an average thickness of the first electrode layer.
8. The multilayer electronic component according to claim 1, wherein The external electrode further includes a plating layer disposed on the second electrode layer.
9. The multilayer electronic component according to claim 1, wherein: The external electrode further includes a conductive resin layer disposed on the second electrode layer and including a conductive metal and a resin.
10. A multilayer electronic component comprising: A main body, comprising a dielectric layer and inner electrodes arranged alternately with the dielectric layer; as well as an outer electrode, disposed on the body, The outer electrode comprises a first electrode layer in contact with the inner electrode and a second electrode layer disposed on the first electrode layer. The first electrode layer includes Cu and a first glass, the second electrode layer includes Cu, SiC and a second glass, and The composition of the first glass is different from the composition of the second glass.
11. The multilayer electronic component according to claim 10, wherein: The first electrode layer includes SiC with an area fraction of less than 1%.
12. The multilayer electronic component according to claim 10, wherein: The first glass includes Ba and Zn, and the second glass includes Si and Al.
13. The multilayer electronic component according to claim 12, wherein: At least a portion of an end portion of the dielectric layer in contact with the first electrode layer includes the first glass.
14. The multilayer electronic component according to claim 10, wherein: At least some of the SiC is spherical.
15. The multilayer electronic component according to claim 10, wherein An average thickness of the second electrode layer is greater than an average thickness of the first electrode layer.
16. The multilayer electronic component according to claim 10, wherein: The external electrode further includes a plating layer disposed on the second electrode layer.
17. The multilayer electronic component according to claim 10, wherein: The external electrode further includes a conductive resin layer disposed on the second electrode layer and including a conductive metal and a resin.
18. The multilayer electronic component according to claim 10, wherein: The area fraction of SiC in the second electrode layer is greater than or equal to 5% and less than or equal to 20%, and the first glass includes Ba and Zn.
19. The multilayer electronic component according to claim 18, wherein: The second glass includes Si and Al.
20. The multilayer electronic component according to claim 19, wherein The second electrode layer further includes an alkali metal or an alkaline earth metal.
Citation Information
Patent Citations
Two-dimensional materials and heterogeneous structures on intermediate polymer transfer layers and their fabrication
KR1020230118899A